Boarding School Learning Management as An Efforts to Create Students with Character - Agus Muhariyoto (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2022)
This study has two purposes; (1) boarding school management at MTS Miftahul Ulum Magersari; (2) boarding school learning as an effort to create students with character at MTS Miftahul Ulum Magersari Plumpang Tuban.This study uses a qualitative approaching (qualitative research), namely is data presented in the form of verbal words not in the form of numbers. Data collection techniques using interviews, observation and documentation. The presence of researchers as an important instrument while still based on the principles of research ethics. The data was analyzed in three steps; data reduction, presentation and conclusion. The results of the study found two models. First, Boarding School Management at MTS Miftahul Ulum is a learning integrates the national curriculum and the foundation curriculum, namely Diniyah Takmiliyah learning, Formal Madrasah, deepen on talent and tahfidz, as well as classical book studies with orderly planning, implementation, and evaluation of learning for all educators. both formal and informal.Second, efforts to create students religiously, disciplined, independent and responsible characters at MTS Miftahul Ulum are carried out through habituation, example, internalization of values, rewards and punishments.